Electron rich porous extended framework as a heterogeneous catalyst for Diels-Alder reactions - Gole, Bappaditya; Bar, Arun Kumar; Mallick, Arijit; Banerjee, Rahul; Mukherjee, Partha Sarathi (Chemical Communications, 2013)
An electron rich porous metal-organic framework (MOF) has been synthesized, which acts as an effective heterogeneous catalyst for Diels-Alder reactions through encapsulation of the reactants in confined nano-channels of the framework.

Evidence of an nN(amide) → π*Ar interaction in N-Alkyl-N,N′-diacylhydrazines - Deka, Jugal Kishore Rai; Sahariah, Biswajit; Sakpal, Sushil S.; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic letters, 2021)
1,2-Dibenzoyl-1-tert-butylhydrazine (RH-5849) and related N-alkyl-N,N′-diacylhydrazines are environmentally benign insect growth regulators. Herein, we show that an unusual n<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">N(amide) → π*<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">Ar interaction mediated by a hydrazide amide nitrogen atom plays a crucial role in stabilizing their biologically active trans–cis (t–c) rotameric conformations. We provide NMR and IR spectroscopic evidence for the presence of these interactions, which is also supported by X-ray crystallographic and computational studies.

Stabilization of Azapeptides by N-amide center dot center dot center dot H-N-amide Hydrogen Bonds - Baruah, Kalpita; Sahariah, Biswajit; Sakpal, Sushil S.; Deka, Jugal Kishore Rai; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic Letters, 2021)
An unusual N-amide center dot center dot center dot H-Namide hydrogen bond (HB) was previously proposed to stabilize the azapeptide beta-turns. Herein we provide experimental evidence for the N-amide center dot center dot center dot H-Namide HB and show that this HB endows a stabilization of 1-3 kcal.mol(-1) and enforces the trans-cis-trans (t-c-t) and cis-cis-trans (c-c-t) amide bond conformations in azapeptides and N-methyl-azapeptides, respectively. Our results indicate that these N-amide center dot center dot center dot H-Namide HBs can have stabilizing contributions even in short azapeptides that cannot fold to form beta-turns.